DEVELOPMENT OF TECHNOLOGY FOR OIL EXTRACTION FROM FAT-CONTAINING WASTES OF FISH PROCESSING IN THE VOLGA-CASPIAN BASIN - M. D. Mukatova; N. A. Kirichko; M. S. Moiseenko; S. A. Skolkov (Известия ТИНРО)
Complete utilization of all wastes of fish processing becomes actual in modern conditions of depletion of the fish raw materials because of the commercial catch decreasing in the Volga-Caspian Basin. Abilities of fish oil extraction from fins of catfish are considered. Several technologies of the oil extraction from this waste are tested: thermal, carbamide-thermal, combined carbamide-thermal, and hydromechanical. Organoleptic parameters of the raw materials and produced fatty products are determined in accordance with the state standard № 7631-2008. Water, protein, fat, and mineral substances content in the raw material and physical and chemical properties of the produced fish oil are measured by standard methods given in the state standard № 7636-85, using the thin-layer chromatography. The fat content in the raw material is evaluated as 33.8 %. The fish oil output from the fat-containing raw materials is determined. The carbamide-thermal method is defined as the optimal one for oil extraction from fins of catfish. At the first stage, the raw material is heated to 70 о C during 60 minutes, then it is mixed with 1.5 % of carbamide in 30 % solution and the liquid and dense fractions of the mixture are separated under 3000 rpm in 30 minutes; at the second stage, the dense fraction is heated to 70°C, mixed with 20 % of water, and the mixture is heated to 75 о C during 60 min, then the liquid and dense fractions of the mixture are separated again; finally, the liquid fractions from both stages of treatment are subjected to sedimentation during 10 minutes under ambient temperature and the semi-finished fatty products are separated by 15 min. centrifuging at 4000 rpm. Phospholipids, monoglycerides, sterols, hydrocarbons, sterol esters, and the main fractions of triglycerides and carotenoids are presented in the fish oil produced with this technology, so it could be used in veterinary. This method for fish oil extraction from the fins of catfish is applied to the enterprises Parshikov and Fabrika Vesna and showed its efficiency in industrial conditions.